Evaluation of monoclonal antibody (IgG2bMAb) for detection of coproantigen from experimentally infected rats with Strongyloides ratti - Noor Abduhaleem; Mahmuda, Aliyu; Tijjani, Mustapha; Abd Majid, Roslaini; Than, Leslie Thian Lung; Unyah, Ngah Zasmy (Sciencedomain International, 2019)
Background and Aim: Highly sensitive and specific diagnostic assay for the detection of Strongyloides is needed due to the intermittent and low concentration of eggs, larvae and adult worms that can be found in a faecal specimen. In some cases, repeated sampling of the faecal specimen is required to obtain satisfactory and reliable results. The aim of the study is to develop and evaluates monoclonal antibody-based Sandwich ELISA for the detection of coproantigen associated with Strongyloides infection using S. ratti as a model.